Unemployment and hair cortisol as a biomarker of chronic stress - Lawes, Mario; Hetschko, Clemens; Schöb, Ronnie; Stephan, Gesine; Eid, Michael (Scientific Reports, 2022)
Unemployment is widely considered an important chronic stressor. Using longitudinal data of initially employed German jobseekers, the present study examines whether unemployment is related to changes in hair cortisol concentration (HCC), a reliable biomarker for chronic stress. The results indicate that HCC is the highest initially when individuals are insecurely employed and decreases as people gain certainty about whether they enter unemployment or not. We find no effects when comparing the average changes in HCC between individuals who entered unemployment to those of continuously employed individuals. However, medium-term unemployment was associated with a stronger mean increase in HCC if re-employment expectations were low compared to when re-employment expectations were high. Taken together, our results support two key conclusions. First, experiencing the uncertainty of looming unemployment is associated with more pronounced cortisol secretion than unemployment itself. Second, whether working or being unemployed is associated with higher HCC is highly context-dependent, with poor re-employment prospects during unemployment being a key predictor of increased HCC. Overall, our study provides further evidence that the physiological stress system is especially sensitive to uncontrollable situations and unfamiliar challenge.
Created from Fastlane, Scopus look-up